Perilaku Menghisap Rokot Elektronik Peserta Didik dan Pengentasan yang Dilakukan Guru Bimbingan dan Konseling - Marta Suhendra (Jurnal Al-Taujih : Bingkai Bimbingan dan Konseling Islami, 2016)
The high rate of smoking behavior by learners is very worrying us. Take up smoking, negative impact on the health of the body, especially for the hearts and minds of learners. Especially with the electronic cigarette in the early discovery used as a tool for reducing addiction to cigarettes that ultimately the WHO as the World Health Organization in 2010 no longer recommend the use of non eloktronik. Departing from the curiosity of students began using poison cigarette smoking eloktronik knowing eloktronik unlike regular cigarettes dangerous toxins. Though the electronic cigarette nicotine is still contained substances hazardous to health and nerve damage bias that exist in the body of learners. Teacher guidance and counseling as one of the educators at the school, have the responsibility to take precautionary action and reduction of the smoking behavior of learners. Guidance and counseling teacher should first give a role model to students in the form of non-smokers, especially in the school environment. Besides counseling and guidance teachers do not miss the development of information and technology, which can make the credulous student teachers. There needs to be cooperation between teacher guidance and counseling with the stakeholders in the school environment and teachers' guidance and counseling should maximize guidance services and schools in each school.